Isolation and characterisation of T lymphocytes from sural nerve biopsies in patients with Guillain-Barré syndrome and chronic inflammatory demyelinating polyneuropathy. - Ben-Smith, A (1996)
OBJECTIVES: To characterise cultured T lymphocytes from nerve biopsies in patients with Guillain-Barré syndrome and chronic inflammatory demyelinating polyneuropathy (CIDP). METHODS: Sural nerve biopsies, obtained from six patients with Guillain-Barré syndrome, four with CIDP, and six controls with other neuropathies, were cultured with 20 U/ml recombinant interleukin-2 (IL-2) for eight weeks. Flow cytometry was used to determine the phenotype of cultured T lymphocytes. Their proliferative responses to a range of bacterial antigens were also examined. RESULTS: T cell lines were established from four of six patients with Guillain-Barré syndrome, one of four with CIDP, one patient with peripheral nerve vasculitis, and none of five controls with non-inflammatory neuropathies. One of these T cell lines from a patient with Guillain-Barré syndrome, preceded by Campylobacter jejuni infection, consisted entirely of gamma delta TCR+ T lymphocytes. The peripheral blood of this patient also contained an increased frequency of gamma delta T cells when stimulated with C jejuni. The nerve derived T cell lines failed to show a proliferative response to bacterial antigens or to a preparation of myelin proteins. CONCLUSIONS: A new technique to isolate T cells from nerve biopsies in patients with Guillain-Barré syndrome and CIDP is reported. This technique may prove to be a useful tool in the investigation of the pathogenesis of other inflammatory neuropathies such as peripheral nerve vasculitis. The isolation of a gamma delta TCR+ nerve T cell line is of interest because of the possibility that these cells might respond to glycolipid epitopes common to C jejuni and peripheral nerve gangliosides.